A experiência de mulheres com o misoprostol no aborto ilegal. - Anne Karoline Borges Silva (2018)
In Brazil, abortion is among the five main causes of maternal mortality. Its criminalization creates health problems and harms the sexual and reproductive rights of women. It is estimated that one in five women at 40 has already had at least one abortion in the country, including women of different beliefs, colors, social classes, with or without children. Misoprostol (Cytotec®) has been the most widely used method for abortion in urban areas and increasing its use has contributed to the decrease in the rate of related complications, allowing the partial abandonment of unsafe techniques, such as the use of sharp objects that can result in uterine perforation. Restricting abortion does not reduce abortion and drives abortion in precarious conditions. This exposes women to avoidable risks and suffering, especially the black, nonwhite, poor and young, in situations of greater social vulnerability. The objective of the study was to describe the experience of the women interviewed with misoprostol in their abortive itineraries in the context of Brazilian restriction, accessing information on the purchase, use and construction of knowledge about the drug, as well as the participation of family members, friends and health professionals in this area. This is a qualitative, phenomenological and feminist study, whose data collection was performed in interviews with six women over 18 years of age who used misoprostol for abortion, who were invited via referral networks in the city of Belo Horizonte, MG. Data were collected from the field diary, socioeconomic questionnaire and semi-structured interviews. The analysis was carried out by means of an exhaustive reading of the transcriptions, identifying common or divergent themes, which configured the thematic categories of work. The interviewees belong to the universe of university higher education, but they are diverse: two white, two brown, two black, with incomes ranging from one to seven minimum wages and age between 22 and 33 years at the time of abortion. Only one is the mother of an eight-year-old boy and two have had two miscarriages. When they became pregnant, they reflected on motherhood, understanding abortion as their best option for unwanted pregnancy, for complex reasons involving future plans, the partner, and family members. They chose the drug because they thought it safe, effective, cheap, and allowed privacy and follow-up. They paid up to 150 reais for each 200 mcg tablet, using it in a private place. Information was accessed by seller, family, and friends' guidelines and / or searches on the internet. Some have contacted support networks on misoprostol, which are important initiatives to help women on how to use it. They bought the drug via the internet or in person from sellers and used it via oral, sublingual or vaginal, according to the information they could access. All patients completed the procedure without sequelae and sought care later to confirm termination of pregnancy. They feared the violence or denunciation, moving away from the professionals who should welcome them. It is pointed out the importance of harm reduction actions, with the availability of accessible information about the medicine, increasing the safety during its use. This issue is also discussed as a public health problem that begins in the field of human rights, permeated by unequal relations of gender, race and class, resulting in the exacerbation of social inequalities, gender violence and restrictions imposed on women's lives. It reflects on the urgency of decriminalization and legalization of the procedure in a secular state, so that women are then recognized as subject to the law. It is understood that from these actions there will be the stimulation of discussions, the elaboration of public policies and effective services focused on nonmoralizing sexual education and reproductive planning, improving the quality of life of the population.